Correlation Between Cytologic Results and Thyroid Autoantibodies, Calcitonin, and Thyroid Function Tests in Patients with Thyroid Nodules (International Journal of Scientific Research and Management (IJSRM), 2018)
Abstract Background: Fine needle aspiration biopsy (FNAB) is currently a widely accepted screening procedure in diagnosis of thyroid nodules, there has been confusion related to diagnostic terminology in the assessment of samples. This confusion has been caused by multiple category names, descriptive reports without assigning to a category, and different terminologies used for surgical pathology. We aimed to evaluate correlations between US characteristics, cytologic results of FNAB, and thyroid antibodies, calcitonin, and thyroid function tests in patients presented with thyroid nodules, and to contribute in diagnosis, treatment, and patient follow-up. Methods: A total of 1639 patients with thyroid nodules who applied to outpatient clinic of endocrinology between dates April and May 2017, had FNAB under US guideline, and their pathologic evaluation was performed according to Bethesda classification. Serological and hormonal tests were also performed for each patient. Results: The mean age of study group was 50 (range interval= 14-90) years. The median of node-diameter1 was 17.5 (range=1-51) mm, and median of node-diameter2 was 12 (range=8-33) mm. Of US characteristics, echogenicity, microcalcification, irregular borders, and solitary nodules were determined in 4.4%, 54%, 71.2%, and 86.6% of cohort respectively. Elevated anti-TPO was determined in 64.6%. Cytologic readings were reported as 15.8% nondiagnostic, 53.8% atypia of undetermined significance/follicular lesion of undetermined significance, 28.8% benign, 0.4% suspicious for follicular nodule, and 1.2% malign. Conclusion: Measurement of thyroid autoantiboides, calcitonin, and thyroid function tests have good correlations with Bethesda classification in patients with thyroid nodules.